'Please sort these voice recordings into 2 identities': Effects of task instructions on performance in voice sorting studies. (22nd July 2019) - Lavan, Nadine; Merriman, Siobhan E.; Ladwa, Paayal; Burston, Luke F.K.; Knight, Sarah; McGettigan, Carolyn
Abstract : We investigated the effects of two types of task instructions on performance on a voice sorting task by listeners who were either familiar or unfamiliar with the voices. Listeners were asked to sort 15 naturally varying stimuli from two voice identities into perceived identities. Half of the listeners sorted the recordings freely into as many identities as they perceived; the other half were forced to sort stimuli into two identities only. As reported in previous studies, unfamiliar listeners formed more clusters than familiar listeners. Listeners therefore perceived different naturally varying stimuli from the same identity as coming from different identities, while being highly accurate at telling apart the stimuli from different voices. We further show that a change in task instructions – forcing listeners to sort stimuli into two identities only – helped unfamiliar listeners to overcome this selective failure at 'telling people together'. This improvement, however, came at the cost of an increase in errors in telling people apart. For familiar listeners, similar non‐significant trends were apparent. Therefore, even when informed about correct number of identities, listeners may fail to accurately perceive identity further highlighting that voice identity perception in the context of natural within‐person variability is a challenging task. We discuss our results in terms of similarities and differences to findings in the face perception literature and their importance in applied settings, such as forensic voice identification.